Comparison of 18F‐FDG PET/CT and 68Ga‐DOTATATE PET/CT in the Targeted Imaging of Culprit Tumors Causing Osteomalacia - Hao‐nan Yu; Ling Liu; Qiu‐song Chen; Qing He; Yan‐sheng Li; Ying Wang; Shuo Gao (Orthopaedic Surgery, 2021)
Objective To assess and compare the performance of fluorine‐18‐labeled fluorodeoxyglucose positron emission tomography (18F‐FDG‐PET/ CT) and gallium‐68‐labeled tetraazacyclododecanetetraacetic acid‐DPhe1‐Tyr3‐octreotate (68Ga‐ DOTATATE) PET/CT in the targeted imaging of culprit tumors causing osteomalacia. Methods This was a clinical retrospective analysis. We analyzed 13 patients (five men, eight women; mean age, 49 years; range, 19–55 years) with suspicion of tumor‐induced osteomalacia (TIO) between March 2017 and October 2019. All patients underwent two functional imaging methods to locate the culprittumors. Studies were performed on a PET/CT scanner. The injection doses of 18F‐ FDG and 68Ga‐DOTATATE were 0.5mCi/kg and approximately 5.0mCi, respectively. In the two scans, the whole body was captured from head to toe 45 to 60 min after intravenous tracer injection. 68Ga‐DOTATATE PET/CT and 18F‐FDG PET/CT imaging results locate culprit tumors according to the following criteria: (i) abnormal foci uptake concentration was observed locally, and the uptake level was higher than the background level of the right lobe of the liver; (ii) combined CT showed or did not have obvious abnormal density changes; and (iii) non‐specific ingestion lesions due to fracture, arthritis, necrosis of femoral head are excluded. Compared with the results of pathological examination and clinical follow‐up, the sensitivity, specificity and accuracy of 68Ga‐DOTATATE PET/CT imaging and 18F‐FDG PET/CT imaging for TIO were analyzed. Results All patients had symptoms of osteomalacia and hypophosphatemia. The lag time (symptoms to PET diagnosis) ranged from 2 to 12 years. There were eight cases of TIO patients and five cases of non‐TIO patients confirmed by surgery, pathology and follow‐up. Among the eight TIO patients, there were six cases (75.0%) of PMTs, one case (12.5%) of giant cell tumor, one case (12.5%) of hemangiopericutoma. Most (n = 6, 75.0%) of the confirmed tumors in our patient population were in the lower extremities, followed by craniofacial regions (n = 1, 12.5%), and torso (n = 1, 12.5%), respectively. Among the five non‐TIO patients, there were two cases of Fanconi syndrome, one case of rickets, and two cases of sporadic osteomalacia hypophosphorus. The culprit tumors could be located either in the bone (n = 5, 62.5%) or the soft tissue (n = 3, 37.5%). 18F‐FDG PET/CT was able to localize the tumor in six (6/13, 46.1%) patients. 68Ga‐DOTATATE PET/CT detected tumor in 8 (83.3%) of 13 patients. The sensitivity of 68Ga‐DOTATATE PET/CT imaging and 18F‐FDG PET/CT imaging in the evaluation of TIO in our patient population were 100% (8/8) vs 75% (6/8). The specificity of the two different methods was 80% (4/5). The overall accuracy was 92.3% (12/13) vs 76.9% (10/13). Conclusions 68Ga‐DOTATATE PET/CT is very effective in assessing hypophosphatemia patients with TIO typical symptoms compared with 18F‐FDG. Therefore, in clinically suspected cases of hypophosphatemic osteomalacia, 68Ga‐DOTATATE PET/CT should be preferred as an imaging modality investigation to avoid delay in the treatment of this disease.